Processo de construção e implantação de um Programa de Educação Permanente em Saúde, voltado ao desenvolvimento do uso de novas tecnologias no campo da saúde: análise de uma experiência em um hospital privado - Cardoso, Rosane Barreto (2015)
Introduction: With the constant increase in new technologies and knowledge in the health field, the Continuing Health Education (CHE) which constitutes a process of analysis and questioning of work, is an effective tool in the incorporation of Information and Communication Technologies (ICT). Objectives: To build and deploy a program of continuing healthcare education focused on the development of the use of new technologies in the health field, as well as identifying the perception of interprofessional health team that took part in training and training on the use of Electronic Patient Record (EPR) on the methodology used and the program of the construction process; the training contribution to the qualification of health care; the use of EPR and its relation with the introduction of ICT in stimulating inter professionalism; and the use of EPR and its relation to the promotion of CHE. Method: Descriptive and exploratory study of quantitative approach, using the attitudinal Likert-type perception instrument for data collection. Results: Four dimensions were built (Dimension-1 "Continuing Education Service as a stimulator of learning area of ICT in health, Dimension-2" The use of ICT in health field as a stimulating tool for interprofessional work, "Dimension-3" The use of EPR and its relation to the promotion of the CHE process" and Dimension-4" The EPR as qualifier tool for health care), containing 17 positive assertions. The attitudinal tool was applied to a population of 71 health care professionals. The instrument reliability test was 0.82 and statistical validation showed loss of one assertion, denoting quality of the validation process content and statistical density. Conclusion: Respondents recognized the importance of the program, as well the EPR as a qualifying element to health care. We emphasize the need for hospitals adopt policies that contribute to the qualification of its professionals, with an emphasis on collaborative and interprofessional work in the light of comprehensive care and sustainability of health for all.